Point of Reckoning The Fight for Racial Justice at Duke University - Segal, Theodore D. (Duke University Press, 2021)
Theodore D. Segal narrates the fraught and contested fight for racial justice at Duke University-which accepted its first black undergraduates in 1963-to tell both a local and national story about the challenges that historically white colleges and universities throughout the country continue to face.